Strategi Pengembangan Desa Digital Untuk Meningkatkan Produktivitas UMKM - Supriyanto, Agus; Hana, Kharis Fadlullah (Universitas Islam Negeri Sunan Kudus, 2020)
The development of online business has increased very rapidly in 2019. Many people who prefer to buy goods online rather than directly. This is a result of the development of increasingly sophisticated technology with the many features of buying and selling online applications. The presence of online stores that make lifestyle changes in society. Ease and efficiency are the main factors in the people's preference for online transactions. Based on that, the purpose of this study is to analyze the obstacles and constraints of MSMEs to join the online store. After getting the results of the analysis then formulate a development strategy. The research method used is descriptive qualitative research object that is the village of Padurenan. The village was chosen because the MSMEs that have been established are very large for the size of one village of 92 units. The results showed that the padurenan village had made a digital village in 2017. The village was able to support from various parties, but when the members were decreasing and there were only 2 MSME members left. The strategy will be developed also by using the principles of Islamic business ethics. Online sales are based on transparency, honesty and fairness. This encourages the realization of sharia maqasid in doing business in the MSME sector.